Assessment of thalassaemia service and community awareness in Kudat district - Osman Ali; Tracy Sein; Naing Oo Tha (Universiti Malaysia Sabah, 2011)
It was estimated that 3-5% of the Malaysian population are Beta-Thalassemia carriers, of which Malays are the majority. This study had probed into the service availability and efforts given in its procedures to detect the cases and carriers and detennine the awareness of Thalassemia among community living in rural area of Sabah, Malaysia. A cross-sectional survey on Thalassemia services was carried out in the hospital and health office of Kudat district, using quantitative and qualitative research methods .It was designed to assess the healthcare service on Thalassemia, characteristics of target population, procedures of services provided, knowledge and opinion of health personnel and communities staying in rural area of Kudat district. Purposive sample of villages were selected for the study, based on the presence of cases from secondary quantitative data. Out of the total 139 respondents, only 89 (60.9%) claimed to know what Thalassemia is but very few had ever tested for Thalassemia. Although half of the participants were aware of Thalassemia, their knowledge on Thalassemia was poor. Some of them knew how Thalassemia was transmitted through carrier of traits which can be diagnosed but did not understand the burden of its chronicity. Most of them had never seen or know about the treatment let alone the prognosis of the illness. Analytical study of the data had shown that there was a statistically significant association between the awareness of Thalassemia and individuals of different ages (p<0.001), occupation (p<0.002) and different education levels (p<0.00 1). In conclusion Thalassemia awareness among the rural community in Sabah, Malaysia was poor despite the high prevalence of the disease carriers. Much effort on Health Education and Health Promotion should be made to improve the awareness of this illness among the rural Malaysian community if the prevalence was to reduce in future.